Stages of development of vocal hearing of younger schoolboys - Kryvonosova, O.V. (Pedagogy of Higher and Secondary Education, 2006)
In article the sequent and stages of development of weal hearing is scientifically proved. Borders of development of vocal hearing at younger schoolboys are established in view of their age features.